Dynamic thermal radiation regulation for thermal management - Guo, Na; Zhao, Ziying; Yan, Hongjie; Chen, Meijie (Next Energy, 2023)
With the improvement of living standards, energy consumption for heating and cooling is increasing. Traditional heaters or coolers (air conditioners etc.) consume lots of energy and only transfer heat to different places on Earth, which increases the ambient temperature and cooling load power. Solar heating and sky radiative cooling by the sun (∼ 5800 K) and outer space (∼ 3 K) have attracted lots of attention recently due to their energy saving and sustainability, which have also shown great potential in thermal management applications for heating and cooling. While the static solar heating or radiative cooling mode would lead to overheating or overcooling in some situations, which may consume more total energy. Therefore, it’s of significance to dynamically regulate thermal radiation by switching heating and cooling modes based on different situations. In this review, the fundamental principles of solar heating and radiative cooling were first introduced to understand the heating and cooling processes in thermal management. Subsequently, the dynamic regulation of thermal radiation was discussed based on active and passive actuation from the solar to mid-infrared spectra. Finally, the potential applications of thermal radiation regulation in building energy savings, smart windows, personal thermal management, and all-day energy harvesting were concluded. Further improvements are still needed to meet the practical applications in terms of the scope and cost of regulation.